2025 Developments in the Rodrigo Duterte Case at the International Criminal Court: Procedural Rigor vs. ICC Jurisdictional Expansionism - Chiarini, Giovanni, Dr (Indonesia Law Review, 2026)
This paper explores the temporal jurisdictional tensions arising from the International Criminal Court’s (ICC) investigation into alleged crimes against humanity committed during President Rodrigo Duterte’s “war on drugs” (2016–2022). Despite the Philippines’ formal withdrawal from the Rome Statute in 2019, the ICC prosecutor proceeded with its investigation, validated by the judges. This raises complex questions surrounding the interpretation of Article 127 of the Rome Statute and the temporal limits of ICC jurisdiction. The paper is divided into three parts: the first outlines the procedural history of the war-on-drugs case, from 2016 to 2024; the second analyzes dissenting judicial opinions cautioning against the broader interpretation of Article 127; and the third examines key 2025 developments, including the issuance of an arrest warrant and public reactions. Ultimately, it argues that the ICC is facing a decisive institutional crossroads. A broader reading of Article 127, combined with the international legal community’s tendency to prioritize substantive justice over procedural formality, risks turning jurisdiction into a political tool.